Implementasi Pendampingan Peningkatan Minat Beli Ulang Dalam Pengembangan Pelayanan Usaha Menengah - Syamlan, Adiba Fuad; Setyorini, Haryati; Syafii, Mochamad; Ilham, Rachmad; Rusdiyanto, Rusdiyanto (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service journal is the output of community service activities that have a topic on customer service by involving the role of students in it. Where this activity aims to provide an overview to students about the application of learning during the lecture process and as another form of guidance to students and the community where this programme takes place. The location of the service is located in the sub-district of Gresik. There are several planning steps that have been conceptualised to support this activity. At the time of implementation, it was found that one of the various obstacles faced was the lack of understanding regarding adequate facilities to support activities and marketing methods that could support increased repurchase interest in medium business development activities which were planned to focus on online and offline-based development. From the activities that have been carried out involving product users, the implementation of activities that have been agreed by both parties is considered to have an influence on increasing repurchase interest.